Retrospective long term outcome following microvascular decompression surgery in Thai patients with trigeminal neuralgia - Prasert Sarnvivad (2018)
Objective: To retrospectively evaluate 5-year pain-free symptoms and clinical outcome for trigeminal neuralgia (TN) patient population after microvascular decompression. Material and Method: The authors reviewed the medical records of all Thai TN cases admitted at Ramathibodi Hospital, Mahidol University, and Ramkhamhaeng Hospital between 2001 and 2006. The 5-year pain-free symptoms and clinical outcome was determined using marginal homogeneity test (Stuart-Maxwell). Results: There were 99 cases with TN. Women (75.6%) were affected more than men (24.4%). More often, the facial pain occurred on the right side of the face (72.8%) than on the left (27.2%). In 78.8% of cases, the facial pain was located along the mandibular division of the trigeminal nerve. In 19.2% of cases, the facial pain was located along the maxilla division of the trigeminal nerve and 30% of cases reported the pain along the combination of the maxilla and the mandibular division of the trigeminal nerve. Two percent of cases located pain along all three divisions. In 65.7% of cases, they reported their trigger points. Thirty-eight cases (38.4%) were operated at Ramkhamhaeng Hospital and 61 cases (61.6%) were diagnosed and treated at Ramathibodi Hospital, Mahidol University. Microvascular decompression surgery was the treatment of choice in all cases. As a final point, 97.9% of all cases who were pain free at the 5-year follow-up were significantly different between before and after treatment (p<0.001). Conclusion: In Thai TN patients, the mandibular division of the trigeminal nerve was most commonly involved, in concordance with other population group studies. In the present study, microvascular decompression surgery is the treatment of choice in TN patient. In the 97.9% of all cases that were pain free at the 5-year follow-up, they were significantly different between before and after treatment (p<0.001).